Institutional Forms to Promote Galicia's Industrial Development in the Era of Autonomy - Kruk, Dariusz Piotr (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
New Institutional Economics is a theory that was cited in the revocation of Galician industrialisation in the era of autonomy. Galicia was a poor area neglected and deprived of organisational structures. The occupying power left the region without the prospect of using the potential of either the people or organizations. However, analysing the region in economic terms, particularly from the point of view of institutions, we see what an important role they played in shaping Galicia's industry. The formal institutions created craft, trade and small-scale industry that caused the region to develop. The article outlines the activity of nationwide industrial associations.